O encontro da Psicologia histórico-cultural com Frantz Fanon: conexões a partir da categoria de sociogenia - Cruz, Margoth Nandes da (2024)
The present research is a theoretical-propositive study, of an exploratory nature, which will address theoretical-methodological issues in the works of Frantz O. Fanon, based on his category of sociogeny, articulating its possible contributions to Cultural[1]Historical Psychology. He was an intellectual, revolutionary and health professional, who studied the relationship between society, social organization - colonialism - and health management, which contributions has been widely studied in Brazil in different areas. The general objective of this research is to understand how the category of sociogeny from Frantz Fanon works contributes to cultural-historical psychology. This is divided into the following specific objectives: 1. Define the category of sociogeny of Frantz Fanon; 2. Contextualize the reality experienced by the author and that composes his theory; 3. Present the theoretical and methodological foundations of Cultural-Historical Psychology and the understanding of the social being; 4. Evaluate the possible contributions of the sociogeny category for the theory and practice based on Cultural-Historical Psychology; 5. Identify the contributions of Fanon's theory to the approach at hand. It is understood that, among the contemporary challenges pointed out in the 2030 Agenda, this research focuses mainly on ODS10, reducing inequalities. The methodology was composed of bibliographic research, based on access to Fanon's works, with emphasis on his period of activity in psychiatry on Algeria. Selective, analytical, and interpretive readings were carried out, along with discussing the relations of similarities and differences between the Fanonian theory and cultural[1]historical psychology were elaborated. Among the findings of the research, the main contribution was identified as the discussion of the exteriority of the body as one of the social aspects that constitute the development of the subject.This study was carried out with the support of the National Council for Scientific and Technological Development - Brazil (CNPq) No. 130106/2022-4